Integration of STEM education in history learning - Rinaldo Adi Pratama; Inne Marthyane Pratiwi; Muhammad Adi Saputra; Sumargono Sumargono (International Journal of Evaluation and Research in Education (IJERE), 2022)
The 21st century needs pupils with learning ability and necessary skills, particularly critical thinking skills instead of content focused. The study of science, technology, engineering and mathematics (STEM) education approach can lead teachers to a new teaching approach in history learning. Through this approach, the teachers can create a new way of teaching history integrated with STEM. This study used a qualitative approach. Data collection in this research using pupil’s work samples, interview, and the teacher journal. This research was conducted in two high school and two vocational school in the urban area. The findings showed that the teachers integrated one of the historical thinking skills and understanding history. The skills are still in the lower level of historical thinking skills. For historical teaching skills to be effectively integrated in history learning, teachers need to be trained so the pupil's historical thinking skills can be enhanced through the integrated history learning with the STEM approach.